Taking a systems approach to groundwater governance in Nepal - Uprety, Labisha (CGIAR System Organization, 2023)
Many groundwater studies focus on the physical aspects of groundwater, including extraction rates, recharge, and water levels. As a social scientist, however, Labisha Uprety, a Senior Research Officer in Policy and Water Governance at the International Water Management Institute (IWMI) in Nepal, recognizes the importance of technical research but is personally more interested in asking questions about water management, governance, and who decides what when it comes to groundwater. These questions are not asked enough in Nepal but could be the key to sustainable groundwater management. As Labisha says, remembering a quote from a 2019 paper by Karen Villholth and co-authors, “the water crisis is a crisis of governance rather than strictly a crisis of resources.”